Generalized integrability and two-dimensional gravitation - Timothy Hollowood (Theoretical and Mathematical Physics, 1992)
We review the construction of generalized integrable hierarchies of partial differential equations, associated to affine Kac-Moody algebras, that include those considered by Drinfel'd and Sokolov. These hierarchies can be used to construct new models of 2D quantum or topological gravity, as well as new $\cal